Increasing Public Awareness Of Embung Biting Sustainability In Sukorame Village, Sukorejo-Pasuruan Through Introduction Of Good And Environmentally Friendly Aquaculture - yuni kilawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2019)
Embung Biting is a native habitat for freshwater fish for Cyprinidae, tilapia, catfish and other endemic fish species. Abundant of natural biological resources including supply of embung water from water sources are very important for meeting the community's water needs. In order to preserve the biological resources of ponds and as a source of fish nutrition for the people of Sukorame Village, it is necessary to be given an understanding to preserve the embung through the introduction of good and environmentally friendly methods of fish farming. This activity has been able to provide an understanding to the community of the importance of sustainability of the embung which is seen in the enthusiasm of the participants and the motivation of the participants to improve entrepreneurial skills in the field of fish farming as alternative livelihoods.